Testing the ability of Porcellionides pruinosus (Brandt 1833) Isopoda Crustaceans to decompose and consume cellulosean wastes in different ecosystems (Baghdad Science Journal, 2012)
The present study was undertaken to use individual terrestrial crustacean from Isopoda such as the species Porcellionides pruinosus (Brandt 1833) as environmental cleaner and that through the test of their abilities in decomposition of residues of some cellulosean wastes such as wood pieces which contain high ratio of urban wastes, and residue of Zea mays and particularly leaves as plant waste in agricultural fields and residue of Cynodon dactylon plants which compose the main wastes in most of gardens and parks. Experiments were conducted relatively in stable laboratory conditions to ensure environmental conditions similar to crustaceans' life. The results showed presence of good efficiency of these individuals in treating such wastes as they consumed 89% of wood pieces and 59% of Zea mays leaves and 27% of residue of Cynodon dactylon plants during the period of treatment. The average of each crustacean individual to consume was 0.74, 0.49 and 0.22 gram from the material mentioned respectively. So, it is recommend to conduct further experiments on different models of agricultural and civil wastes by using different species of these organisms to carry out such studies with a broad spectrum in future to treat the wastes and pollutants of environment by biological approach.